Using Kids Coloring Fun Application to enhance Children Vocabulary Mastery at Tumbuh Kembang Kindergarten - Muhammad Chairil Imran; Nasaruddin Nasaruddin (South Sulawesi Education Development (SSED), 2021)
The research was mainly discussing the use of Kids Coloring Fun Application to enhance the vocabulary mastery of children in the Tumbuh Kembang Kindergarten. The researchers selected the sample from the population by using total sampling technique. The number of the sample was 40 children. This research was a pre-experimental design with one group pretest and posttest. The group was tested after treatment, the test included pretest and posttest that consisted of 25 items. The result of data analysis showed that there was a significant difference between the mean scores of pretest and posttest. The mean score of posttest was greater than the mean score of pretest. The means score of pretest was 5.06 and the mean score of posttest was 8.07. Then, the T-test value was 25.5 and T-table value was 2.042 with df = 39 and α = 0.05. It can be concluded that the use of Kids Coloring Fun Application can enhance children vocabularies. It means that there is a significant difference (H1) of the children vocabularies before and after treatment by using Kids Coloring Fun Application.